Physicochemical property enhancement of biodiesel synthesis from hybrid feedstocks of waste cooking vegetable oil and Beauty leaf oil through optimized alkaline-catalysed transesterification. (October 2018) - Milano, Jassinnee; Ong, Hwai Chyuan; Masjuki, H.H.; Silitonga, A.S.; Kusumo, F.; Dharma, S.; Sebayang, A.H.; Cheah, Mei Yee; Wang, Chin-Tsan
Graphical abstract: Highlights: Biodiesel is produced from waste cooking oil and Calophyllum inophyllum oil. The optimum process parameters maximize the WC70CI30 biodiesel yield (94.12%). The WC70CI30 biodiesel has high oxidation stability (22.4 h). The WC70CI30 biodiesel has good cold flow properties comparable to diesel. The WC70CI30 biodiesel has physicochemical properties superior to WC biodiesel. Abstract: Recycling waste cooking vegetable oils by reclaiming and using these oils as biodiesel feedstocks is one of the promising solutions to address global energy demands. However, producing these biodiesels poses a significant challenge because of their poor physicochemical properties due the high free fatty acid content and impurities present in the feedstock, which will reduce the biodiesel yields. Hence, this study implemented the following strategy in order to address this issue: (1) 70 vol% of waste cooking vegetable oil blended with 30 vol% of Calophyllum inophyllum oil named as WC70CI30 used to alter its properties, (2) a three-stage process (degumming, esterification, and transesterification) was conducted which reduces the free fatty acid content and presence of impurities, and (3) the transesterification process parameters (methanol/oil ratio, reaction temperature, reaction time, and catalyst concentration) were optimized using response surface methodology in order to increase the biodiesel conversion yield. The results show that the WC70CI30 biodiesel has favourable physicochemical properties, good cold flow properties, and high oxidation stability (22.4 h), which fulfil the fuel specifications stated in the ASTMD6751 and EN 14214 standards. It found that the WC70CI30 biodiesel has great potential as a diesel substitute without the need for antioxidants and pour point depressants.